Geologia e litogeoquímica de migmatitos, charnockitos e granulitos do Complexo Guaxupé na região de São João da Boa Vista (SP) - De Melo, Rodrigo Prudente [UNESP]; De Oliveira, Marcos Aurélio Farias [UNESP] (FapUNIFESP (SciELO), 2013)
This paper presents new geochemical and petrological data from the southern portion of the Guaxupé Complex. The research area is characterized by the occurrence of migmatites and an intrusive body of charnockitic granite located on the northeastern portion of the area. Petrological and geochemical studies of the banded migmatites have shown that the paleossome is generally composed by tholeiitic basaltic orthogranulite showing island arc signature. Partial melting of these basic orthogranulites has formed calc-alkalic neossome of granitic to tonalitic composition with high SiO2 content (> 68.9%) and high (La/Lu)N ratios, as well as low K/Rb ratios. These features are coherent to partial melting of Rb-rich basic protholits at temperatures around 820C producing a felsic melt in presence of orthopyroxene and clinopyroxene. Moreover, a geochemical study of a rocks suite from the charnockitic intrusion has pointed out that its evolution is characterized by magmatic differentiation through crystal fractionation process, which, in turn, has formed a magmatic series starting with porphyritic granite, followed by charnockitic gneiss and leucogneiss as the final product of crystal fractionation. These rocks, located geographically close to the magmatic intrusion, must have been formed by partial melting of granulitic crustal rocks of dioritic composition, represented by banded granulitic gneisses with a geochemical signature similar to the magmatic rocks.
Geology and lithogeochemistry of migmatites, charnockites and granulites of the Guaxupé Complex, São João da Boa Vista region, São Paulo State, Brazil
Keywords: Charnockitic gneiss; Granulite; Guaxupé Complex; Migmatite